ESG performance and carbon emission intensity: examining the role of climate policy uncertainty and the digital economy in China’s dual-carbon era - Li, Shiyu; Ao, Xiangyuan; Zhang, Mengdie; Pu, Mingyue (Frontiers in Environmental Science, 2025)
In line with the Sustainable Development Goals (SDGs) proposed by the United Nations and the general direction of global green and low-carbon transformation, China has formulated a dual-carbon target. It aims to peak carbon dioxide emissions by 2030 and strive for carbon neutrality by 2060. Therefore, carbon emission intensity (CEI) has gradually become a research focus. This study investigates the effect of ESG performance on CEI, and explores the moderating effect of climate policy uncertainty (CPU) and the digital economy (DE) on ESG performance and CEI. Provincial-level data in China from 2011 to 2020 was used under the panel data analysis method. The analysis reveals that ESG performance significantly alleviates CEI. In addition, CPU weakens the efficiency of ESG initiatives in decreasing CEI due to regulatory unpredictability, while the digital economy’s expansion, although innovative, may exacerbate CEI in regions dependent on fossil fuels. The study contributes to the literature by highlighting the need for integrated policies that harmonize digital growth with sustainability goals. Additionally, it underscores the significance of considering CPU and DE as critical moderating factors in ESG-CEI dynamics, offering insights for policymakers aiming to balance technological advancement with environmental responsibility.